THE MAJLIS DHIKR OF INDONESIA: Exposition of Some Aspects of Ritual Practices (JOURNAL OF INDONESIAN ISLAM, 2009)
This study will explore the extent to which Indonesian Majlis Dhikr groups interpret and respond theologically certain aspects of their ritual practices. Several topics discussed in this paper wish to answer whether or not the belief and ritual of Majlis Dhikr are relevant to the normative dimension of Islamic teachings and Islamic Sufi practices. This research reveals that some aspects of Sufi practices have been adopted by Majlis Dhikrthe groups in their main ritual practices have a strong basis in the practices of the Prophet and Sufi masters. I argue that what they have practised actually cannot be regarded as the violation of Islamic teachings as has been frequently accused by other groups of Muslims. Some aspects of Sufi practices and concepts adopted by Majlis Dhikr group include the reciting of salawat, the concepts of sainthood (wali) and miracle (karamah), tawassul, sending the merit of pious deeds to deceased persons, and the concept of tabarruk.